Renal Parenchymal Volumetric Expansion Assessed by CT Imaging After Laparoscopic Cyst Decortication - Gültekin, Mehmet Hamza; Yalcin, Ahmet; Erbay, Guven (Urology Journal, 2020)
Purpose: To delineate the expansion of the renal parenchyma using volumetric CT imaging before and after the laparoscopic cyst decortication procedure and to determine the possible associations between parenchymal expansion and laboratory parameters and cyst volume. Materials and Methods: Thirty-five patients that underwent laparoscopic cyst decortication were included in this prospective study. Abdominal contrast-enhanced CT was performed in all patients in the preoperative and postoperative period. Semi-automatic volume quantification was undertaken offline, and renal parenchymal volumes before and after cyst decortication, as well as serum creatinine and estimated glomerular filtration rate (eGFR) were compared. Results: The changes in serum creatinine and eGFR in the postoperative period were non-significant. The mean postoperative renal parenchymal volumes were higher compared to the preoperative measurements for both observations (P = .014 and .034 for the first and second measurements, respectively). There was no correlation between the volumetric change and the cyst volume (r = -0.18, P = .560). Conclusion: In patients undergoing laparoscopic cyst decortication, post-operative parenchymal expansion can be detected using volumetric CT imaging to confirm the immediate benefits of the procedure.